Problem-Solving Ability Profile of Phase E Students Through the Application of the PBLWVL Model - Agus Danawan; Yuli Yulianti (CV. Edujavare Publishing, 2026)
This research is motivated by the implementation of the Independent Curriculum in high schools that requires Phase E students to understand physics concepts, have science process skills, and have problem-solving abilities. The purpose of this study is to determine the description of how aspects of problem-solving abilities include: visualization of problem descriptions, physics approaches, specific applications of physics concepts, mathematical procedures, and logical conclusions, after the application of learning with the Problem Based Learning with Virtual Laboratory (PBLWVL) model. The PBLWVL model was implemented in phase E of Grade X on the topic of energy conversion and the Law of Conservation of Energy. With Virtual laboratory referred to in the learning process using PhET simulation. This study used a quantitative Pre-Experimental method using a One Group Pretest Posttest Design research design. The sample in this study amounted to 33 students at one of the public high schools in Bandung City. The instrument used was 20 essay questions to measure the increase in problem-solving abilities. The research data were analyzed using N-gain. The results of the study showed that there was an average increase in students' problem-solving abilities of 0.69 with a moderate increase category, with the indicator of the ability to apply specific physics concepts having high criteria (score 0.95).